Mutagenicity and antimutagenic activities of lactic acid bacteria (LAB) isolated from fermented durian (tempoyak) - Asmariah Ahmad; Safura Salik; Yap, Wei Boon; Noorhisham Tan Kofli; Ahmad Rohi Ghazali (Penerbit Universiti Kebangsaan Malaysia, 2018)
Mutagenic and antimutagenic activities of lactic acid bacteria (LAB) Lactobacillus plantarum isolated from the local fermented durian (tempoyak) was determined by Ames test (Salmonella/microsome mutagenicity assay). Our study also involved pre-incubation assay against Salmonella typhimurium TA 98 and TA 100 bacterial strain in the presence and absence of metabolic activator S9 system. It was found that the L. plantarum showed no mutagenic activity on both S. typhimurium strain TA 98 and TA 100 in the presence and absence of metabolic activator. Significant antimutagenic activity (p < 0.05) was observed in both cell-free supernatant and bacterial cell suspension of L. plantarum as compared to the mutagenicity induced by 2-Aminoanthracene in the presence of metabolic activator. Meanwhile, in the absence of metabolic activator, only the bacterial cells of L. plantarum showed antimutagenicity acitivity against Sodium Azide and 2-Nitrofluorene. In conclusion, L. plantarum could play a vital role as chemopreventive agent by binding to mutagens and suppressing mutagenesis. Thus, L. plantarum could be consider as a good candidate for functional food development as a supplement product to prevent development of colon cancer.